Effectiveness of Student Learning in the Department of Office Automation and Governance at SMK Darussalam Makassar - Haedar Akib; Fitri Sari Untung; Muh. Nasrullah; Baharuddin Baharuddin (Pinisi Journal of Education and Management, 2022)
Education has a very important role in human life and becomes very important in achieving goals, in practice the learning process carried out becomes something that can be used in achieving these goals. Learning is one of the most basic elements in the implementation of education, the success or failure of an education will depend on how the learning process is given by the teacher. One of the goals of the school is to create quality human resources so that they are able to adapt and compete in the world of work. The current condition requires the ability and expertise that must be possessed by every individual, especially soft skills which will later support job opportunities. This study aims to determine how the effectiveness of learning in students majoring in Office Administration Automation (OTKP) at SMK Darussalam Makassar. The main activity in the education system in the school environment is a learning activity. The implementation of the learning mechanism can be done through three types of educational environment, namely informal, formal and non-formal. Data collection techniques consist of observation, interview and documentation methods. Data analysis techniques in this study are data reduction, data presentation and conclusion drawing. The results of the study show that it is quite effective even though the current situation is all-new with more use of IT in the learning process.